THE REALIZATIONS OF VIOLATION MAXIMS BY MAIN CHARACTERS IN KELUARGA BETI COMEDY SERIES - Asrah . Raihana; Amrin . Saragih; Rahmad . Husein (LINGUISTIK TERAPAN, 2022)
This study deals with the realizations of violation maxims of main characters in Keluarga Beti comedy series. The objectives of the study were to describe realization of violation maxims used by main characters in Keluarga Beti comedy series. This research was conducted by qualitative design. The data were sentences of main characters which were violated. The data source of this research was taken from Keluarga Beti comedy series that was obtained from the video on YouTube. The finding of the data showed eleven realizations of violation maxim of main characters in Keluarga Beti comedy series as understating, overstating, using tautologies, contradiction, using irony, give hints, give association clues, be ambiguous, overgeneralize, and overstating and be ambiguous. The most dominant realization of violation maxim was being ambiguous. The less dominant realized of main characters in Keluarga Beti comedy series were understating and give association clues. The absence of the realizations of main characters in Keluarga Beti comedy series were metaphor, presuppose, and be vague. The researcher also found other realizations were unrelated statement and combination of overstating and be ambiguous. Keywords:Violation Maxims, Main Characters, Comedy, Keluarga Beti Comedy Series.